Junior weightlifters' age-specific neuro-muscular system performance profiling study - Dvorkin, L. S.; Dvorkina, N. I.; Popova, S. I. (Theory and Practice of Physical Culture, 2018)
Presently the research literature on the subject provides little if any trustworthy data on the electrokymographic tests of the junior weightlifters` age-specific neuro-muscular system performance rates. Objective of the study was to profile the junior weightlifters` age-specific neuro-muscular system performance rates. Subject to the study were junior (13-14 year-old) weightlifters (n=14) forming Experimental Group (EG) versus Reference Group (n=23, RG) of their non-sporting peers. Tests under the study were designed to obtain wrist dynamometric data for the dominant/ non-dominant arms versus the bioelectrical activity of the following muscles: musculus flexor carpi radialis, musculus flexor carpi ulnaris, musculus brachialis and musculus palmaris longus. The groups were requested to apply 1/3 of the maximal strength till the last moment when the static tension could still be kept at the required level. The junior athletes were tested with gradual growth of the total bioelectrical muscle activity rates in the wrist strength tests versus the their non-sporting peers tested with falling bioelectric muscuar activity rates - that may be indicative of the athletes` nervous mechanism control system operating more efficiently i.e. the muscular performance control by the CNS being better developed versus their non-sporting peers.